(untitled) (Research, Society and Development, 2021)
Recognizing high abilities in less favored social classes is a challenge because children in vulnerable conditions can be left out in social and educational settings. The objective of the article was to verify in Brazilian and international databases whether there are scientific productions about high abilities in vulnerable environments. A systematic review of the productions was carried out on the following databases: Scientific Eletronic Library Online (Scielo); Periódicos Eletrônicos em Psicologia (PePSIC); Revista Educação Especial, and finally at EBSCO host, applying the search filter: Academic Search Complete, Education Resources Information Center (ERIC) and Psycarticles. As a result, it was obtained, 4 (four) Brazilian articles and 14 (fourteen) international articles. The productions found are related to several themes, such as: poverty, prisoners or those who commit infractions, homelessness and school vulnerability or at social risk, and the most reported theme in the research was high capacities and poverty. Based on the researches, could be inferred that high abilities and vulnerability are themes still poorly studied, which may lead to believe in a lack of identification and attention for these children, adolescents and adults from vulnerable environments and, consequently, resulting in a loss of his talents.